Universalism vs. Relativism. The Phenomenological Foundation of Ethics according to Scheler - Chu García, Mariana (2014)
How  to  interpret  and  elucidate  from  a  phenomenological  perspective  the  requirement  that  philosophical theorizing ought to  consider  the  legitimacy  or universal validity  of  ethical  principles  as  well  as the diversity of life forms? What could phenomenology say about the distance between  the  theoretical  foundations  of  ethics  and  the  practical  application  of its principles? To elucidate these questions, first, we take the characteristics of Habermas’s discourse ethics as reference point to show what Scheler’s material ethics of values consists in and in what sense it rejects both universalism and relativism. Secondly, we present the concepts that articulate the phenomenological foundations of this ethics in order to indicate in what sense “the universal” and “the individual” are taken as complementary. Starting from some questions concerning the problem of the distance between theory and practice raised by this conception, we sketch finally some thematic lines to indicate to what extent it is possible to expect from the material ethics of values to shorten that distance.